Human uracil-DNA glycosylase complements E. coli ung mutants. - Olsen, L C (1991)
We have previously isolated a cDNA encoding a human uracil-DNA glycosylase which is closely related to the bacterial and yeast enzymes. In vitro expression of this cDNA produced a protein with an apparent molecular weight of 34 K in agreement with the size predicted from the sequence data. The in vitro expressed protein exhibited uracil-DNA glycosylase activity. The close resemblance between the human and the bacterial enzyme raised the possibility that the human enzyme may be able to complement E. coli ung mutants. In order to test this hypothesis, the human uracil-DNA glycosylase cDNA was established in a bacterial expression vector. Expression of the human enzyme as a LacZ alpha-humUNG fusion protein was then studied in E. coli ung mutants. E. coli cells lacking uracil-DNA glycosylase activity exhibit a weak mutator phenotype and they are permissive for growth of phages with uracil-containing DNA. Here we show that the expression of human uracil-DNA glycosylase in E. coli can restore the wild type phenotype of ung mutants. These results demonstrate that the evolutionary conservation of the uracil-DNA glycosylase structure is also reflected in the conservation of the mechanism for removal of uracil from DNA.